2018
DOI: 10.28991/cej-0309133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry-wet Cycle on the Formation of Loess Slope Spalling Hazards

Abstract: This paper investigates the effect of dry-wet cycle process on the formation of loess slope spalling hazards. Based on the CT scan tests and macroscopic fissures analysis, the fissure variation law of loess samples under different dry-wet cycle times were determined. Through the laboratory direct shear tests, the variation law of shear strength, cohesion and angle of internal friction of loess samples under different dry-wet cycle times and different dry-wet cycle water content variation ranges were discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…However, there are also some differences. Ye et al 17 showed that there were numbers of cracks and pitting on the surface of loess samples after three cycles, while the vegetation concrete substrate showed cracks on the surface after 12 cycles because cement was added into it. Previous studies 8 have shown that the gelling material produced by the cement hydration reaction could reduce the pore volume of the substrate and increase the inter-particle connection.…”
Section: R E T R a C T E D Discussionmentioning
confidence: 99%
“…However, there are also some differences. Ye et al 17 showed that there were numbers of cracks and pitting on the surface of loess samples after three cycles, while the vegetation concrete substrate showed cracks on the surface after 12 cycles because cement was added into it. Previous studies 8 have shown that the gelling material produced by the cement hydration reaction could reduce the pore volume of the substrate and increase the inter-particle connection.…”
Section: R E T R a C T E D Discussionmentioning
confidence: 99%
“…Experimental studies have shown that the strength and erosion resistance of soil significantly decreases after FT cycles, and continuous FT action exacerbates the degradation, which leads to high erodibility and denudation sensitivity under thawing (Liu et al, 2017; Wang et al, 2020). Based on the laboratory mechanical tests of undisturbed and remolded loess after FT cycles, the loess cohesion was reported to decrease exponentially with the FT action, while the variation range of internal friction angle was limited (Xu, Ren, et al, 2018; Ye et al, 2012). Research on the microstructure of frozen soil has revealed the micromechanical properties of soil via microscopic observations (Qi et al, 2006), showing FT cycles to destroy the larger aggregates in soil (Song et al, 2017; Xiao et al, 2019), break the connection between the particles, gradually weaken the bonding strength and decrease (increase) the large (small) pores (Ni & Shi, 2014; Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature differences generated by the short-term diurnal and long-term seasonal changes have resulted in a continuous freeze-thaw cycle, deteriorating the physical and mechanical properties of the soil [3][4][5]. In addition, the impacts of human engineering activities have led to frequent spalling, landslides, and other common issues on the loess cut-slopes in the region, seriously harming the ecological environment along the loess cut-slopes and impeding the coexistence of humans and nature [6][7][8]. Therefore, understanding how the loess in northern Shaanxi degrades during freeze-thaw cycles and identifying the destructive influences on loess cut-slopes could have significant theoretical and practical implications for the engineering design and management of loess cut-slopes in areas with seasonally frozen soil.…”
Section: Introductionmentioning
confidence: 99%